5th June 3rd Sunday after Pentecost - Plant, Stephen (2016)
This article offers a reflection on a Gospel Reading from 1 Kings 17.8-16, Psalm 146, Galatians 1.11-24 and Luke 7.11-17, the appointed verses for June 3, 2016: the 3rd Sunday after Pentecost. Topics discussed include why the "new" is almost always preferred to the "old" in consumerist cultures, the role played by prophet Jeremiah in originating the terms "Old Testament" and "New Testament," and how apostles Luke and Paul used the Old and the New in their writings about Jesus Christ.
Keywords: Bible. Galatians; Bible. Luke; Bible. Psalms; Consumerism; JEREMIAH (Biblical prophet)